2021
DOI: 10.51982/bagimli.806920
|View full text |Cite
|
Sign up to set email alerts
|

Ergenlerde İnternet Bağımlılığı ile Şema Mekanizmaları Arasındaki İlişki

Abstract: Objective: The aim of this study was to investigate the relationship between internet addiction and schema mechanisms of adolescents in a private high school sample. Method: The study sample was based on a relational screening model with the participation of 148 volunteer students in a private Anatolian High School located in Üsküdar district of Istanbul province in the 2015-2016 Academic year. Data was collected using the Internet dependency scale, Young schema scale, and sociodemographic data form. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
2
0
4
Order By: Relevance
“…In another study, it is found that the internet usage purposes of adolescents are generally "having fun/spending time", "communicating" and "obtaining information" (Günlü & Ceyhan, 2017). In the study by Aksoy & Ünübol (2021), it was found that the majority of adolescents use the internet for entertainment (such as gaming, watching TV) and communication purposes. Öztürk (2021), on the other hand, stated in his study that students mostly use the internet to access social media.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it is found that the internet usage purposes of adolescents are generally "having fun/spending time", "communicating" and "obtaining information" (Günlü & Ceyhan, 2017). In the study by Aksoy & Ünübol (2021), it was found that the majority of adolescents use the internet for entertainment (such as gaming, watching TV) and communication purposes. Öztürk (2021), on the other hand, stated in his study that students mostly use the internet to access social media.…”
Section: Discussionmentioning
confidence: 99%
“…Çıkan bulgularda internet bağımlılığı düzeyleri ile cinsiyet arasında anlamlı bir farklılık tespit edilememiştir. Literatürde benzer bulgulara ulaşmak mümkündür (Aksoy ve Ünübol, 2021;Anlayışlı ve Serin, 2019;Aslan, 2019;Tekin, 2020;Topçu, 2020;Yüksel, vd., 2020). Bazı araştırmalarda ise İnternet bağımlılığı ile cinsiyet arasındaki ilişki erkeklerin lehine anlamlı çıkmıştır (Derin, 2013;Sevinç ve Taş, 2020;Şahin, vd., 2017;Taşlıyan, vd., 2018;Yüksel ve Yılmaz, 2016).…”
Section: Cinsiyetunclassified
“…Ereğli Eğitim Fakültesi Dergisi [28] internete erişemediği durumlarda öfke, sinir ve huzursuzluk duygu durumlarının belirmesine neden olmaktadır. Bu durum, bireylerin gündelik ihtiyaç ve sorumluluklarını ihmal etmelerine neden olmaktadır (Aslan, 2019;Aksoy ve Ünübol, 2021).…”
unclassified
See 2 more Smart Citations